Intraoperative end-tidal carbon dioxide levels are not associated with recurrence-free survival after elective pancreatic cancer surgery: a retrospective cohort study - Dehne, Sarah; Kirschner, Lina; Klotz, Rosa; Kilian, Samuel; Michalski, Christoph; Hackert, Thilo; Büchler, Markus W.; Weigand, Markus A.; Larmann, Jan (Frontiers in medicine, 2024)
Background Intraoperative end-tidal carbon dioxide concentrations (EtCO2) values are associated with recurrence-free survival after colorectal cancer surgery. However, it is unknown if similar effects can be observed after other surgical procedures. There is now evidence available for target EtCO2 and its relation to surgical outcomes following pancreatic cancer surgery. Methods In this single-center, retrospective cohort study, we analyzed 652 patients undergoing elective resection of pancreatic cancer at Heidelberg University Hospital between 2009 and 2016. The entire patient cohort was sorted in ascending order based on mean intraoperative EtCO2 values and then divided into two groups: the high-EtCO2 group and the low-EtCO2 group. The pre-specified primary endpoint was the assessment of recurrence-free survival up to the last known follow-up. Cardiovascular events, surgical site infections, sepsis, and reoperations during the hospital stay, as well as overall survival were pre-specified secondary outcomes. Results Mean EtCO2 was 33.8 mmHg ±1.1 in the low-EtCO2 group vs. 36.8 mmHg ±1.9 in the high-EtCO2 group. Median follow-up was 2.6 (Q1:1.4; Q3:4.4) years. Recurrence-free survival did not differ among the high and low-EtCO2 groups [HR = 1.043 (95% CI: 0.875-1.243), log rank test: p = 0.909]. Factors affecting the primary endpoint were studied via Cox analysis, which indicated no correlation between mean EtCO2 levels and recurrence-free survival [Coefficient −0.004, HR = 0.996 (95% CI:0.95-1.04); p = 0.871]. We did not identify any differences in the secondary endpoints, either. Conclusions During elective pancreatic cancer surgery, anesthesiologists should set EtCO2 targets for reasons other than oncological outcome until conclusive evidence from prospective, multicenter randomized controlled trials is available.